Feasibility Evaluation of a Long-Life Asphalt Pavement for Steel Bridge Deck - Leilei Chen; Zhendong Qian; Daoxie Chen; Ya Wei (Advances in Civil Engineering)
In order to extend the service life of the steel bridge deck pavement, a long-life steel bridge deck pavement (LLSBDP) was put forward referring to the concept of long-life asphalt pavement. First, the requirements of the LLSBDP were given, based on which, an LLSBDP structure “EAC + SMA” was proposed. Second, a numerical analysis was performed to evaluate the stress status of the “EAC + SMA” structure. Third, an experimental study was conducted to assess the performance of the pavement material and the pavement structure. Meanwhile, for comparison, the performances of traditional steel bridge deck pavement structure “EAC + EAC” were also studied in the numerical and experimental program. The results showed that, with periodical rehabilitation or reconstruction of the SMA surface layer, the EAC base layer can last for a long life without structural distresses. The proposed structure can meet the requirements of LLSBDP and can be used to extend the service life of the steel bridge deck pavement.